Shipbuilding transfer of technology model from the recipient prospective - Jayaraman, Prebagaran (2009)
This longitudinal qualitative case study identifies the receiver caused barriers in International Transfer of Technology (ToT) program involving PSC-ND’s New Generation Patrol Vessel Project from Germany to Malaysia. In line with qualitative research methodology, a number of data sources and data collection methods were employed. Observation of individual Technical Procurement Specification meetings with technology source and regular attendance at the weekly project progress review meeting was part of this study. The author was involved with the organizations from the inception of the ToT project. Events were observed as they unfolded and the researcher was often present when decisions were being made in response to these events and the eventual outcomes reported. Apart from attending management meetings information was gathered from interviews and other relevant documents as well as author’s field notes based on observation and informal discussion. A total of 60 interviews were conducted lasting about one hour with participants of the ToT program, senior management staff and Technology Source mainly representative of OEM, Training Subcontractors from Australia and German Naval Group. Interviews were taped and transcribed. Data analysis involving data reduction, display and verification were undertaken throughout the duration of the study. Analysis of the data resulted in development of various themes that interpret the meaning of data. The research identified that both the government Joint Monitoring Committee and PSC-ND Project Managers’ contributed to the poor project management practices in the ToT Management. Besides lack of formal ToT Management, the research identified various barriers in the key activities of Identification of Technology of Interest, Technology Acquisition, Technology Absorption and Adaptation and Technology Innovation. The study has recommended a comprehensive ToT Management Model to effectively manage ToT.